The Role of Project-Based Learning in Developing Professional Culture of Future Art Teachers - Toshmuhammedova Iroda Alibek qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the role of project-based learning in enhancing the professional culture of future art teachers. By engaging in practical and collaborative projects, students develop artistic skills, pedagogical competencies, and socio-cultural awareness. The study highlights methods for integrating project-based approaches into art education, fostering creative thinking, aesthetic development, and professional identity formation.